Triptolide-Loaded Mesenchymal Stem Cell–Derived Exosomes Ameliorates Lipopolysaccharide-Induced Acute Lung Injury via Induction of Nrf-2/HO-1 Signaling Pathway–Dependent Autophagy and Mitigation of MAPK Signaling Pathway - Ying Zhang; Fan Pan; Xiaotao Xu; Zhihua Jiao; Hong Xie; Aizhong Wang (Canadian Respiratory Journal)
Acute lung injury (ALI) is a severe disease characterized by a pulmonary inflammatory response and oxidative stress. Triptolide has been demonstrated to have anti-inflammatory and antioxidant properties. Herein, we present triptolide-loaded mesenchymal stem cell–derived exosomes (MSC-Exos) as a multifunctional biomimetic delivery system (Tri-Exos) for targeting injured lung tissue. The therapeutic effect of Tri-Exos on ALI was evaluated by measuring inflammatory cytokines content, the expression of myeloperoxidase (MPO), the number of immune cells in bronchoalveolar lavage fluid, malondialdehyde (MDA) content, and superoxide dismutase (SOD) activity. Subsequently, immunohistochemistry and Western blotting were used to assess the expression levels of critical proteins in the nuclear factor erythroid 2-related factor 2 (Nrf-2) signaling pathway, autophagy pathway, apoptosis, and MAPK signaling pathway. The experimental results showed that LPS significantly increased pathological damage, secretion of inflammatory cytokines, and oxidative stress in lung tissue. However, treatment with Tri-Exos significantly alleviated this series of pathological changes. Tri-Exos significantly upregulated the expression of Nrf-2 signaling pathway–related proteins, autophagy, and apoptosis and inhibited the expression of MAPK signaling pathway-related proteins in the ALI model. Our study showed that Tri-Exos exerted a therapeutic effect on LPS-induced ALI by regulating the Nrf-2 signaling pathway–dependent autophagy and MAPK signaling pathway.